Bioactivity-guided separation of the active compounds in acacia pennata responsible for the prevention of Alzheimer's disease - Pattamapan Lomarat (2018)
The objective of this study was to evaluate the health benefits of plants used in Thai food, specifically Acacia pennata Willd., in Alzheimer's prevention. A. pennata twigs strongly inhibited β-amyloid aggregation. Bioactivity-guided separation of the active fractions yielded six known compounds, tetracosane (1), 1-(heptyloxy)-octadecane (2), methyl tridecanoate (3), arborinone (4), confertamide A (5) and 4-hydroxy-1-methyl-pyrrolidin-2-carboxylic acid (6). The structures were determined by spectroscopic analysis. Biological testing revealed that tetracosane (1) was the most potent inhibitor of β-amyloid aggregation, followed by 1-(heptyloxy)-octadecane (2) with IC 50 values of 0.4 and 12.3 μM. Methyl tridecanoate (3), arborinone (4) and 4-hydroxy-1-methyl-pyrrolidin-2-carboxylic acid (6) moderately inhibited β-amyloid aggregation. In addition, tetracosane (1) and methyl tridecanoate (3) weakly inhibited acetylcholinesterase (AChE). These results suggested that the effect of A. pennata on Alzheimer's disease was likely due to the inhibition of β-amyloid aggregation. Thus A. pennata may be beneficial for Alzheimer's prevention.